2003
DOI: 10.1016/s0735-1097(03)00329-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced external counterpulsation improves endothelial function in patients with symptomatic coronary artery disease

Abstract: Enhanced external counterpulsation enhances peripheral endothelial function with beneficial effects persisting at one-month follow-up in patients with a positive clinical response. This suggests that improvement in endothelial function may contribute to the clinical benefit of EECP in patients with symptomatic CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
313
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 373 publications
(336 citation statements)
references
References 34 publications
12
313
1
3
Order By: Relevance
“…This method has been validated and described previously in other populations16, 17, 18, 19, 20 and in patients with AF 21. After a 5‐minute baseline measurement, the blood pressure cuff on the test arm was inflated to 60 mm Hg above baseline systolic blood pressure or a maximum of 200 mm Hg for 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…This method has been validated and described previously in other populations16, 17, 18, 19, 20 and in patients with AF 21. After a 5‐minute baseline measurement, the blood pressure cuff on the test arm was inflated to 60 mm Hg above baseline systolic blood pressure or a maximum of 200 mm Hg for 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…7 More recently, Bonetti et al did demonstrate an improvement in peripheral endothelial function that persisted up to 1 month after treatment. 8 Although related to endothelial function, arterial stiffness may vary in an endothelial-independent manner in different subjects. 23 On the other hand, several studies have demonstrated increased myocardial perfusion with associated release of endothelial growth factors, improved coronary endothelial function, and decreased neurohumeral factors, which may reflect improved ventricular hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…3 Improved coronary 7 and, more recently, peripheral endothelial function have been demonstrated up to 1 month after therapy. 8 Left ventricular diastolic function and endothelial function are related to arterial stiffness, 9,10 but no study to date has examined the effect of EECP on large artery stiffness. Arterial stiffness or compliance can be measured noninvasively by a number of methods, including pulse wave velocity (PWV) and pulse wave analysis.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing interest in the use of EECP in patients with established coronary disease for whom EECP might be used as an alternative to traditional revascularization, extending to a potential role in secondary and primary prevention of cardiovascular events. 7 Currently, EECP treatment is largely restricted to patients with refractory and severely disabling angina partly because of reimbursement coverage of only patients with CCS class III and IV angina by the Centers for Medicare and Medicaid Services (CMS). The present study was conducted to evaluate the potential benefit of EECP in treating refractory patients with less severely disabling (CCS class II) angina.…”
Section: Introductionmentioning
confidence: 99%